THE COMPOSITION OF ZIRCON AND IGNEOUS AND METAMORPHIC PETROGENESIS - Hoskin P.W.O.; Schaltegger U. (My University, 2003)
Zircon is the main mineral in the majority of igneous and metamorphic rocks with Zr as an essential structural constituent. It is a host for significant fractions of the whole-rock abundance of U, Th, Hf, and the REE (Sawka 1988, Bea 1996, O’Hara et al. 2001). These elements are important geochemically as process indicators or parent isotopes for age determination. The importance of zircon in crustal evolution studies is underscored by its predominant use in U-Th-Pb geochronology and investigations of the temporal evolution of both the crust and lithospheric mantle. In the past decade an increasing interest in the composition of zircon, trace-elements in particular, has been motivated by the effort to better constrain in situ microprobe-acquired isotopic ages. Electron-beam compositional imaging and isotope-ratio measurement by in situ beam techniques—and the micrometer-scale spatial resolution that is possible—has revealed in many cases that single zircon crystals contain a record of multiple geologic events. Such events can either be zircon-consuming, alteration, or zircon-forming and may be separated in time by millions or billions of years. In many cases, calculated zircon isotopic ages do not coincide with ages of geologic events determined from other minerals or from whole-rock analysis. To interpret the geologic validity and significance of multiple ages, and ages unsupported by independent analysis of other isotopic systems, has been the impetus for most past investigations of zircon composition. Some recent compositional investigations of zircon have not been directly related to geochronology, but to the ability of zircon to influence or record petrogenetic processes in igneous and metamorphic systems. Sedimentary rocks may also contain a significant fraction of zircon. Although authigenic zircon has been reported (Saxena 1966, Baruah et al. 1995, Hower et al. 1999), it appears to be very rare and may in fact be related to …
Keywords: Zircon